Management Information System for Department of Iron and Steel Ministry of Steel, Mines and Metals Volume -1 System Description - Planning Commission (Planning Commission, 1968)
The Management Information System for the Department of Iron & Steel, outlined in this report, was developed by the Management and Project Evaluation Division at the instance of the Department of Iron and Steel. The object of the system is to provide the Department with a rationalised method of performance reporting which would identify the major problems in the operation of the three steel plants of Hindustan Steel Limited, together with the corrective action being undertaken in the company. The work on system design was initiated in August 1967 with a series of discussions with the senior officials in the Department of Iron & Steel on the existing reports and data flowing into the Department from the three plants and the Hindustan Steel Head Office.
Management & Project Evaluation Division Committee on Plan Projects Planning Commission